ROCK MINEROLOGICAL ANALYSIS OF PAWON CIPATAT CAVE, WEST BANDUNG - Dimas Lanang Bayushakti (Jurnal Scientia, 2023)
This study aims to analyze the mineralogy of the rocks found in Pawon Cipatat Cave, West Bandung Regency. Pawon Cipatat Cave is one of the caves located in Cipatat area, West Java, Indonesia. This research is important to understand the mineral composition of the rocks that make up this cave and to gain better information about the geological history and processes that formed the cave. The research method used involved taking rock samples from various locations in the cave. The results of the study show that in Pawon Cave the constituent rocks are limestone, the main element of which is the CaCO3 carbonate compound. While the minerals consist of phosphates, oxides and hydroxides, sulfides, silicates, and carbonates. This research provides a deeper understanding of the mineralogical characteristics of the Pawon Cipatat Cave rocks and provides new insights into the geological history of the cave. The results of this research can also be useful in studying the formation processes of other caves in the area and can make an important contribution to regional geological research